Appropriate Switching State Selection to Avoid Capacitor Imbalance in Five-Level NPC - Kuthuri Narasimha Raju; Chandra Sekhar Obbu; Ramamoorthy M (Institute of Advanced Engineering and Science, 2018)
An intrinsic problem with neutral point clamped (NPC) multilevel inverters (MLI) is unbalance of capacitor voltage. There are many mitigation techniques well established in the literature to balance the neutral point voltage for 3-level inverter. These techniques employ either Carrier based pulse width modulation (CBPWM), Space vector pulse width modulation (SVPWM) or hybrid of both the PWM techniques. Balancing becomes complicated as the level of the inverter increases due to addition of capacitor junctions. The imbalance in capacitor voltages may cause uneven voltage distribution among switching devices and sometimes may cause failure. It also increases harmonic content in its output waveform. This paper develops new modulation scheme for balancing capacitor voltages for Five-level inverter .The scheme is a hybrid PWM which is a combination of both CBPWM and SVPWM techniques. As per this scheme CBPWM is applied to meet the load demand and at the zero crossings of the reference signal, CBPWM is blocked and for one carrier cycle. During this SVPWM is applied with appropriate switching state selection to neutralize the imbalance in capacitor voltage.